The Mechanical Behavior of Fiber Reinforced PP ECC Beams under Reverse Cyclic Loading - Yaw ChiaHwan; Han JianBo (Advances in Materials Science and Engineering)
When a structure is hit by earthquake, tremendous amount of seismic energy is released and structure is subjected to reverse loads. The mechanical properties of FRP reinforced PP ECC beams and coupon RC beam under reverse cyclic load controlled by displacement are investigated. Curing ages, reinforcement ratio, and volume fraction of PP fiber are parameters under survey. It is shown that multiple saturated cracking occurred in PP ECC beam and no crushing appeared. The PP ECC can enhance strength and energy dissipation capacity which are important to evaluate the performance of structures subjected to reverse cyclic loading.